Recognition of Iron Overload Cardiomyopathy - QU Nan; LIU Ting; ZHANG Qing (罕见病研究, 2023)
Iron overload cardiomyopathy (IOC) is a type of cardiac dysfunction caused by several factors resulting in iron overload in the myocardium. Two major causes of IOC include hereditary hemochromatosis and transfusion-dependent anemia. IOC significantly reduces long-term survival of patients. Since IOC is a rare disease in Asian populations that also lacks etiology-specific manifestations, early diagnoses in clinical practice are challenging. Two groups of patients with high risk of IOC should be further investigated: those who present heart failure of unknown origin will be screened for iron overload followed by confirmation of IOC; and those who have high risk of iron overload or an established diagnosis will be monitored for the development of IOC. Serum ferritin is recommended as the first-line screening test for iron overload, while cardiac magnetic resonance T2* should be used to confirm iron overload in the myocardium. Phlebotomy and iron chelating agents can effectively remove the extra iron from the body, preventing IOC, as well as reverse the disease at an early stage and slow down its progession. Timely diagnosis and treatment is critical in improving the prognosis of patients with IOC. Therefore, this review aims to help clinicians to understand IOC in multiple dimensions including pathogenesis, clinical manifestations, diagnostic methods and treatment choices.